Hepatitis B Virus Infection Is Associated with a Higher Risk of Liver Metastasis in Gastric Cancer. - Zhu, Songting; Jiang, Mengmeng; Chen, Yanyan; Ding, Yongfeng; Wang, Haiyong; Teng, Lisong (Current Oncology, 2026)
Simple Summary: Hepatitis B virus (HBV) is not only associated with primary liver cancer but also increases the risk of other malignancies, and may be linked to an increased risk of liver metastasis in colorectal cancer. However, the relationship between HBV infection and liver metastasis in gastric cancer (GCLM) remains unclear. This retrospective study focuses on the relationship between HBV infection and liver metastasis in gastric cancer. This study shows that hepatitis B virus infection increases the risk of liver metastasis in gastric cancer patients. Patients with HBV infection should receive careful monitoring for liver metastasis to improve clinical management and outcomes. Background: Hepatitis B virus infection has been linked to liver cancer and may influence metastasis in other malignancies, but its role in gastric cancer liver metastasis (GCLM) is unclear. Methods: We retrospectively analyzed 776 gastric cancer patients with HBV testing. HBV infection was defined as HBsAg+ (chronic HBV, CHB) or HBsAg− with HBcAb/HBeAb+ (occult HBV, OHB). Among the 776 patients, 300 (38.6%) were classified as HBV+. The association between HBV infection and GCLM was evaluated, and propensity score matching (PSM) was performed to adjust for age and gender. Furthermore, the impact of HBV infection on overall survival (OS) was analyzed. Results: GCLM occurred in 19.5% of patients. HBV+ patients had a higher GCLM prevalence than HBV− patients (25.3% vs. 15.8%; p = 0.001), persisting after PSM (25.3% vs. 15.3%; p = 0.002). HBV infection was an independent risk factor for GCLM (OR = 2.563, p < 0.001). Both OHB and CHB groups showed significantly higher GCLM rates than HBV− patients in univariate and multivariate analyses. However, OS did not differ between groups (p = 0.737). Conclusion: HBV infection significantly increases the risk of liver metastasis in gastric cancer. Enhanced surveillance for liver metastasis is warranted in these patients.